Computer simulation of bubble formation - Insepov, Z.; Bazhirov, T.; Norman, G.; Stegailov, V. (Joint International Topical Meeting on Mathematics & Computation and Supercomputing in Nuclear Applications, 2007)
Properties of liquid metals (Li, Pb, Na) containing nanoscale cavities were studied by atomistic Molecular Dynamics (MD). Two atomistic models of cavity simulation were developed that cover a wide area in the phase diagram with negative pressure. In the first model, the thermodynamics of cavity formation, stability and the dynamics of cavity evolution in bulk liquid metals have been studied. Radial densities, pressures, surface tensions, and work functions of nano-scale cavities of various radii were calculated for liquid Li, Na, and Pb at various temperatures and densities, and at small negative pressures near the liquid-gas spinodal, and the work functions for cavity formation in liquid Li were calculated and compared with the available experimental data. The cavitation rate can further be obtained by using the classical nucleation theory (CNT). The second model is based on the stability study and on the kinetics of cavitation of the stretched liquid metals. A MD method was used to simulate cavitation in a metastable Pb and Li melts and determine the stability limits. States at temperatures below critical (T < 0.5Tc) and large negative pressures were considered. The kinetic boundary of liquid phase stability was shown to be different from the spinodal. The kinetics and dynamics of cavitation were studied. The pressure dependences of cavitation frequencies were obtained for several temperatures. The results of MD calculations were compared with estimates based on classical nucleation theory.
Keywords: bubble; cavity; liquid metals; nucleation theory; simulation